Manajemen Pemasaran dan Manajemen Usaha bagi Kelompok Wanita Tani Pembuat Telur Asin dan Telur Asin Asap di Kabupaten Hulu Sungai Tengah - Gusti Marliani; Ernawati Ernawati; Khairiyahtul Anwar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Eggs resulting from cattle used for nutritional consumption and sold as the family income. To make eggs durable, a group of farmers women change it into the salted egg and smoke salted egg (intalu jaruk). An increase in business management by making the profile and structure partner organizations. This event is held for four months since may and Agust 2016. The targets for the event are groups of farmers women maker eggs duck salted smoke as many as 2 groups that are groups of farmers women melati village kalibaru subdistrict Batu benawa and groups of women farmers mufakat village hilir banua kecamatan pandawan Kabupaten Hulu Sungai Tengah South Kalimantan. Application of science and technology for the is expected to adopted by a group partner in their entirety with direct involvement between teams devotion with groups of women farmers Melati and groups of women farmers mufakat maker salted egg and salted egg smoke. The implementation of the program devotion it is developed to strategically with focus groups discussion with a partner, training, counseling, technical assistance, evaluation and monitoring of the program the application of science and technology The results of this activity is increasing knowledge, ability, and skill in the management of marketing and business management. In addition, it products of leaflets or brochures, a signboard, packaging, and brands, profile business and structure organization.